Implementation of Management Information Systems in Managing Educational Institutions: Chances and Challenges - Ridwan, M. Kholil; Hidayati, Nur (International Journal of Multidisciplinary Research of Higher Education, 2025)
The implementation of management information systems in managing educational institutions plays an important role in improving the efficiency and quality of management. The implementation of management information systems in madrasah in the face of educational disruption that has occurred globally. This study aims to analyze the implementation of management information systems in managing educational institutions. This research uses a qualitative method with a case study approach. Data analysis was conducted using the Miles & Huberman model. The results of this study show that one educational institution has succeeded in taking advantage of the great opportunities in the implementation of management information systems to face educational disruption. This success was realized through strengthening the technological infrastructure which reached 60%, as well as increasing the mastery of human resources by 30%. The implementation of this system also accelerates data-based decision-making that supports the quality of education services. However, challenges remain, albeit minimal. The findings of this study provide important implications for improving education management in madrasahs. The implementation of management information systems enables the digitalization of administration, improving efficiency, transparency and data-based decision-making.